The most important contaminants of air pollutants in Klang station using multivariate statistical analysis - Zakaria, Haslina; Sharif, Shamshuritawati (IP Publishing LLC, 2019)
Air pollution is a crucial subject that needs responsiveness from all relevant authorities as it is one of the major factors that disturbing public health, agricultural industries, forest species and environments. Thus, it is important to determine the most significance contaminants to monitor the air quality. In this study, the daily data of contaminants suspended in the air which are particulate matter (PM), and various gases such as ozone (O3), nitrogen oxides (NO2), sulphur dioxide (SO2), and carbon monoxide (CO) are used. It is covering a four year time period from 2011 until 2014 that vetained from the Malaysian Department of Environment (DOE). Multivariate statistical analysis such as a radar plot, correlation analysis and principal component analysis is used to determine the most significant contaminants for the air-pollutant. From the study, it can be concluded that that Nitrogen Oxides (52%) is the most influential contaminant of air pollutants followed by Particulate Matter (43.9%) and Carbon Monoxide (43.3%).